Opportunities for life course research through the integration of data across Clinical and Translational Research Institutes. Issue 3 (1st October 2018) - Hanson, Heidi A.; Hay, William W.; Tobin, Jonathan N.; Barkin, Shari L.; Atkins, Mark; Karagas, Margaret R.; Dozier, Ann M.; Wetmore, Cynthia; Konstan, Michael W.; Heubi, James E.
Abstract : Introduction: Early life exposures affect health and disease across the life course and potentially across multiple generations. The Clinical and Translational Research Institutes (CTSIs) offer an opportunity to utilize and link existing databases to conduct lifespan research. Methods: A survey with Lifespan Domain Taskforce expert input was created and distributed to lead lifespan researchers at each of the 64 CTSIs. The survey requested information regarding institutional databases related to early life exposure, child-maternal health, or lifespan research. Results: Of 64 CTSI, 88% provided information on a total of 130 databases. Approximately 59% (n=76/130) had an associated biorepository. Longitudinal data were available for 72% (n=93/130) of reported databases. Many of the biorepositories (n=44/76; 68%) have standard operating procedures that can be shared with other researchers. Conclusions: The majority of CTSI databases and biorepositories focusing on child-maternal health and lifespan research could be leveraged for lifespan research, increased generalizability and enhanced multi-institutional research in the United States.